2019
DOI: 10.3164/jcbn.19-11
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of α-cyclodextrin-stabilized 4-methylthio-3-butenyl isothiocyanate from daikon (<i>Raphanus sativus</i> var. <i>longipinnatus</i>) in mice

Abstract: unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. 4 Methylthio 3 butenyl isothiocyanate (MTBI) is a pungent bio active constituent found in daikon. However, MTBI is immediately hydrolyzed to 3 hydroxy methylene 2 thioxopyrrolidine in grated daikon. In this study, we evaluated whether MTBI in grated daikon complexed with α cyclodextrin (αCD) has anti obesity effects in mice. C57BL/6J mice were fed a normal diet (normal group), high fat diet (HFD, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the positive intake of BCAAs, GLS, and ITC has been reported to lower the risk of type 2 diabetes (Bahadoran et al., 2012; Kurotani et al, 2013; Kuzuya et al., 2008). A recent animal study has also demonstrated the anti‐obesity effect of the radish root‐derived MTBITC (Okamoto et al., 2019).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, the positive intake of BCAAs, GLS, and ITC has been reported to lower the risk of type 2 diabetes (Bahadoran et al., 2012; Kurotani et al, 2013; Kuzuya et al., 2008). A recent animal study has also demonstrated the anti‐obesity effect of the radish root‐derived MTBITC (Okamoto et al., 2019).…”
Section: Resultsmentioning
confidence: 98%